2014
DOI: 10.1159/000368460
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in Renalase and Blood Pressure Responses to Dietary Salt and Potassium Interventions: A Family-Based Association Study

Abstract: Background/Aims: Renalase (gene name RNLS), a recently discovered enzyme with monoamine oxidase activity, is implicated in the degradation of catecholamines. Recent studies indicate that common variations in the gene with RNLS are associated with hypertension. The aim of this study was to examine the association between genetic variants in RNLS and blood pressure (BP) responses to strict dietary interventions of salt and potassium intake. Methods: A total of 334 subjects from 124 families were selected and seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 28 publications
1
25
0
3
Order By: Relevance
“…These results were demonstrated by our recent studies, in which we found that high-salt diet causes a significant decrease in serum renalase levels and increase in urinary renalase secretion in Chinese adults [16,17]. In addition, we recently showed that polymorphisms of the renalase gene were associated with blood-pressure (BP) responses to dietary salt intake in a family-based study [18]. However, the relationship between salt intake and renalase expression has not been fully established and deserves further investigation.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…These results were demonstrated by our recent studies, in which we found that high-salt diet causes a significant decrease in serum renalase levels and increase in urinary renalase secretion in Chinese adults [16,17]. In addition, we recently showed that polymorphisms of the renalase gene were associated with blood-pressure (BP) responses to dietary salt intake in a family-based study [18]. However, the relationship between salt intake and renalase expression has not been fully established and deserves further investigation.…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, the source of urine renalase is not fully documented. Our family-based association study identified several single-nucleotide polymorphisms of the renalase gene, namely, rs919115, rs792205, and rs12356177, which were associated with BP responses to changes in dietary salt intake [18]. In a study by Fedchenko et al [24] that involved SHR, the kidney renalase mRNA in rats with a moderate increase in BP (140 mm Hg) did not change as much as that in the control rats.…”
Section: Discussionmentioning
confidence: 99%
“…A familybased association study found that genetic variants in the RNLS gene were associated with BP responses to dietary salt intake [67]. High-salt intake increased vasoconstrictor 20-hydroxyeicosatetraenoic acid excretion, which potentially mediated the early-phase high-salt diet-induced BP elevation [68]. Up-regulated intrarenal rennin-angiotensin system might contribute to high-salt induced hypertension and renal damage [69].…”
Section: Unhealthy Dietary Factors Contribute To Metabolic Hypertensionmentioning
confidence: 99%
“…However, in another study in haemodialysis patients, renalase gene rs2576178 polymorphism was not associated with blood pressure [17]. Significant data data was published by Wang et al [18], describing the association between multiple SNPs in renalase gene (rs919115, rs792205, rs12356177) and blood pressure responses to changes in in dietary salt intake. There is also a study confirming the association of the renalase gen SNP and hypertension in a group of patients with diabetes mellitus type 2 [19].…”
Section: Renalase and Hypertensionmentioning
confidence: 97%